The Contemporary Chinese Policy in Southeast Asia - N. V. Vlasov (Vestnik MGIMO-Universiteta)
Although the PRC has been gradually turning into a genuinely global power recently, her regional interests particularly in SEA are not shrinking. Developing relations with ASEAN in general and its member states in particular is still among the key priorities of the Chinese foreign policy. This is motivated by the interest to ensure safe and controlled buffer along China's border perimeter - "belt of peace, stability and common prosperity". At present, Chinese standing in SEA is firm. Sino-ASEAN relations are based upon mutual pragmatism. The reason for that to a great extent is a tangible trade and economic and investment cooperation. Bilateral relations in political and security as well as defense spheres have been also steadily expanding. Humanitarian ties are closely interwoven, which may help make future ASEAN elites more pro-Chinese. Nevertheless, it has been all the more evident that Southeast Asian nations are seeking to lower their current overdependence on China. Their concern are rising due to China's growing political and military and economic muscles as well as because of increasing Chinese nationalism. Unresolved territorial disputes in the South China Sea also impede promotion of China's influence there. In this context China turns out to be sandwiched between the necessity to uphold her national interests, on the one hand, and the goal to keep a comfort regional atmosphere for facilitating her relationship with ASEAN, on the other. Moreover, lately there has been another sound factor jeopardizing China's leadership in SEA - Washington's Asia Pacific pivot.